APPLICATION OF OPEN-SOURCE SOFTWARE AND LOW-COST HARDWARE IN THE VIDEO SURVEILLANCE - Valdés Alfonso, Jonathan Raidel (Telemática, 2020)
The main goal of this paper is the validation of the use of open-source software and low-cost hardware in the equipment of audio and video capture. To achieve this, we discuss the design of an audio and video capture equipment using the low-cost SBC (Single Board Computer) Raspberry Pi 3B, the Pi Camera V.2 modules for the video capture and the capture of the audio, the two channels AD converter with USB interface using Audio class AK5371. This design will be useful to support the implementation of a camera for video surveillance. The software architecture is divided into two layers, one for user interaction using the framework for the development of web applications Flask, and another layer that implements the stages of acquisition, processing, and streaming of the data, to be used by the multimedia application framework GStreamer. This design represents an alternative to commercial equipment, using open-source software and low-cost hardware.